Children’s Cognitive Development and Breastfeeding: Synthesis and Review of Literature - Adeleke, Owoade Philip; Ogabor, Joseph Odey; Ekaette, Samuel Okpon; Orim, Samuel Orim; Okoye, Joy Sade; Sanda, Francis Ademola; Ewa, James Abua; Udie, Lazarus Ishifundi; Ani, Augustine Undiugweundemaye; Ogar, Raymond Ogbebe; Olofu, Precilla Alu; Ikwen, Emmanuel Umiuya; et al. (International Journal of Child Health and Nutrition, 2026)
This literature review synthesizes empirical evidence from 10 studies published between 2016 and 2025 to examine the relationship between breastfeeding and cognitive development in early childhood. The review aims to elucidate the extent to which breastfeeding influences cognitive outcomes while accounting for moderating factors such as socioeconomic status, maternal education, and genetic predispositions. Utilizing a systematic methodology, the review analyzes study designs, sample characteristics, measurement tools, and key findings. Results indicate a consistent positive association between breastfeeding duration and cognitive performance, particularly in language and executive functions, although this association is moderated by environmental and familial factors. Limitations include potential confounding variables, reliance on self-reported data, and variability in assessment methods. The review concludes that breastfeeding may be a significant contributor to early cognitive development, warranting policies that promote breastfeeding. Future research should focus on longitudinal designs and causal mechanisms to better understand this relationship.